Preliminary quantification of the in situ performance of a novel hydrogen peroxide based explosive. (3rd April 2017) - Onederra, Italo; Araos, Miguel
Abstract: This paper reports the results of a preliminary monitoring program designed to quantify the in situ performance of newly developed hydrogen peroxide based explosives. Their advantage is that they do not produce NOx fumes upon detonation. Direct measurements of velocity of detonation, pressure, temperature and displacement were obtained. Detonation velocities ranged from 2607 to 5100 m s −1 with differences mainly attributed to density variations. The data showed consistent relative differences in pressure and temperature with measurements in the range of 0.6–2.6 GPa and 2036–3551 °C respectively. Multiple hole tests showed that there was no adverse impact on product behaviour such as dead pressing or desensitisation. Video analysis confirmed that displacement was prominent in single hole crater tests but limited in multiple hole tests. Observations confirmed that new fracturing and dilation of discontinuities was evident; with relative differences in fragmentation associated with changes in rock mass conditions.